PhytoKeys - PENSOFT Publishers (Pensoft, 2010)
PhytoKeys is a peer-reviewed, open-access journal launched to accelerate research and free information exchange in taxonomy, phylogeny, biogeography and evolution of higher plants and lichens. Journal will publish papers in systematic botany containing taxonomic/floristic data on any taxon of any geological age from any part of the world.
Keywords: Plants : Classification : Periodicals; Plants : Nomenclature : Periodicals; Lichens : Classification : Periodicals; Lichens : Nomenclature : Periodicals; Botany : Periodicals; Biodiversity : Periodicals; Biodiversity; Botany; Lichens : Classification; Plants; Plants : Classification; Classification; Phylogeny; Botany - General